THE SIGNIFICANCE OF MULTIFOCAL ATHEROSCLEROSIS IN THE COURSE OF ISCHEMIC HEART DISEASE AND IMPAIRMENT OF KIDNEY FUNCTION - Rakhimova M.E; Nobo’toyev O.M (Scholar Express Journals, 2023)
Although the term atherosclerosis is widely used in practice, the resulting damage occurs at different levels and in the order of the vessels in different areas, depending on the age, gender and comorbidities of the patients. In most cases, the atherosclerotic process develops in the aorta, heart, brain, kidneys, internal and external carotid arteries, hip and knee arteries. In addition, the pathogenic mechanisms and risk factors (RF) of atherosclerotic vascular injury in different basins are the same, although the presence and importance of each risk factor in this situation differ. Accordingly, high serum cholesterol levels are important for coronary atherosclerosis, stroke is associated with arterial hypertension (AH) and kidney damage, and vascular damage in the legs is associated with diabetes and smoking. An organic relationship was found between renal artery stenosis and diabetes mellitus (DM). Often the cooccurrence of these diseases is due to the fact that they have many common risk factors. In this case, there is a high risk of rapid and irreversible deterioration of renal function and difficulty in treatment.
Keywords: ischemic heart disease; atherosclerosis; renal artery stenosis